Seleção de bactérias para fermentação malolática de vinhos - Luz, Giovanni Colussi da (My University, 2018)
Brazilian wines, mainly from Rio Grande do Sul, often have high acidity due to the different maturation of the grapes. This acidity is determined by high concentrations of malic acid. In order to attenuate the fixed acidity in the wines, the musts are subjected to malolactic fermentation during or after the alcoholic fermentation. In oenological practice, this fermentation represents problems, occurring in an uncontrolled way and in many cases not coming to an end. Although often efficient, spontaneous malolactic fermentation, depending on the bacteria present in the grape or canteen, varies from fermentation to fermentation and from year to year, and is now one of the critical points in the winemaking process. Strains of Oenococcus oeni and Lactobacillus sp., Species of lactic bacteria, are predominant in this fermentation process. Parameters such as pH, sulfur dioxide (SO2), alcohol content and temperature are the most important that affect the performance of these bacteria in wine. Other bacterial species may add undesirable characteristics to the final product, such as the production of bioactive amines, impertinent odor and bacteriocins that inhibit malolactic fermentation. This work aimed at the selection and identification of native lactic bacteria from the Serra Gaúcha wineries. A total of 34 bacteria were isolated from samples of malolactic fermentation, of which only 16 were classified as lactic acid. Not all 16 bacteria obtained good growth in liquid medium. The fermentative glucose test with evaluation of acid and gas production showed that some isolates did not acidify or produce gas. Already the carbohydrate fermentation test, which used 14 carbohydrates, found that the bacteria have a preference inmetabolizing disaccharides and monosaccharides. In the fermentative tests in synthetic wort, some isolates were able to significantly alter the pH, reducing the cidity, but did not present turbidity. The malolactic fermentation in this experiment was accompanied qualitatively in paper chromatography and, even with growthproblems, some isolates were able to effect a good malolactic fermentation. With respect to the evaluation of the sensitivity to potassium metabisulphite (K2S2O5), different pH levels and different concentrations of ethanol, the isolates were better eveloped at lower concentrations of K2S2O5 and lower alcoholic strength. PH levels near 3.5 were preferred for bacterial development. The existence of microvinification in synthetic wine with 10% ethanolic degree, only by four isolates that demonstrated good malolactic fermentation in must, certified that the lower the alcohol concentration, the lower the interference in the fermentation. In this experiment, the degradation was evaluated qualitatively / quantitatively, using paper chromatography and enzymatic kit. There was a change in pH, confirming the conversion of malic acid to lactic acid by all isolates. The final classification of the isolates included the species Lactobacillus suebicus, Lactobacillus pentosus and Lactobacillus plantarum
Os vinhos brasileiros, principalmente do Rio Grande do Sul, apresentam, muitas vezes, elevada acidez decorrente da maturação diferente das uvas. Esta acidez é determinada por altas concentrações de ácido málico. Para atenuar a acidez fixa nos vinhos, os mostos são submetidos à fermentação malolática durante ou seguidamente a fermentação alcoólica. Na prática enológica, essa fermentação representa problemas, ocorrendo de forma descontrolada e em muitos casos não chegando a finalizar. Ainda que muitas vezes eficiente, a fermentação malolática espontânea, dependente das bactérias presentes na uva ou na cantina, varia de fermentação para fermentação e de ano para ano, sendo hoje um dos pontos críticos no processo de vinificação. Estirpes de Oenococcus oeni e Lactobacillus sp., espécies de bactérias láticas, são predominantes nesse processo fermentativo. Os parâmetros como pH, dióxido de enxofre (SO2), conteúdo alcoólico e temperatura são os mais importantes que afetam o desempenho dessas bactérias no vinho. Outras espécies bacterianas podem adicionar características indesejáveis no produto final, como a produção de aminas bioativas, odor impertinente e bacteriocinas que inibem a fermentação malolática. Esse trabalho visou a seleção e identificação de bactérias láticas nativas de vinícolas da Serra Gaúcha. Foram isoladas 34 bactérias provenientes de amostras de vinhos que se encontravam em fase de fermentação malolática, e dessas, apenas 16 foram classificadas como láticas, pois apenas essas apresentaram características de catalase negativa, Gram positivas e imóveis. Nem todas as 16 bactérias obtiveram bom crescimento em meio líquido. O ensaio fermentativo de glicose com avaliação da produção de ácido e gás demonstraram que alguns isolados não acidificaram e nem produziram gás. Já o teste de fermentação de carboidratos, que utilizou 14carboidratos, constatou que as bactérias possuem preferência em metabolizar dissacarídeos e monossacarídeos. Nos testes fermentativos em mosto sintético, alguns isolados conseguiram alterar significativamente o pH, reduzindo a acidez, porém não apresentaram turbidez. A fermentação malolática nesse experimento foi acompanhada qualitativamente em cromatografia de papel e, mesmo com problemas de crescimento, alguns isolados conseguiram efetuar uma boa fermentação malolática. Com relação à avaliação da sensibilidade ao metabissulfito de potássio (K2S2O5), diferentes níveis de Ph e diferentes concentrações de etanol, os isolados desenvolveram–se melhor nas concentrações mais baixas de K2S2O5 e em graduação alcóolica menor. Os níveis de pH próximos a 3,5 foram os preferidos para o desenvolvimento bacteriano. A existência da crovinificação em vinho sintético com grau etanólico de 10%, apenas por quatro isolados que demonstraram boa fermentação malolática em mosto, certificou que quanto menor a concentração de álcool, menor também é a interferência na fermentação. Nesse experimento avaliou-se a degradação málica quali/quantitativamente, com utilização de cromatografia de papel e kit enzimático. Houve alteração de pH, comprovando a conversão do ácido málico em lático por todos os isolados. A classificação final dos isolados os enquadrou com as espécies Lactobacillus suebicus, Lactobacillus pentosus e Lactobacillus plantarum.
Keywords: Vinho e vinificação; Fermentação; Wine and wine making; Fermentation; Bacterías; Bacteria